2011
DOI: 10.1111/j.1468-3083.2010.03740.x
|View full text |Cite
|
Sign up to set email alerts
|

The practical use of cytology for diagnosis in dermatology

Abstract: Exfoliative cytology for diagnostic purposes is rarely used in Dermatology despite the rapid and reliable results which this procedure can offer in many clinical conditions. This simple procedure may prove advantageous in a wide range of skin diseases, including genodermatoses (Hailey-Hailey disease), infections (mainly herpetic infections, molluscum contagiosum, leishmaniasis), immune disorders (early oral pemphigus) and tumours (basal and squamous cell carcinomas, Paget disease, erythroplasia of Queyrat, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 16 publications
0
41
0
10
Order By: Relevance
“…Awareness of characteristic cytological features can help in reaching a correct diagnosis even in a clinically unsuspected case. 11 The previous experience of the cytopathologist with cytodiagnosis of MC was helpful in the present case reported here. 5 …”
Section: Figure 2bmentioning
confidence: 65%
“…Awareness of characteristic cytological features can help in reaching a correct diagnosis even in a clinically unsuspected case. 11 The previous experience of the cytopathologist with cytodiagnosis of MC was helpful in the present case reported here. 5 …”
Section: Figure 2bmentioning
confidence: 65%
“…The results of a meta-analysis have demonstrated that this test has a very high sensitivity (97%, 95% CI 94 -99) and specificity (86%, 95% CI 80 -91) (20). The high accuracy of TST for margin control was encouraging to propose an applied evaluation alternative approach for well-demarcated BCC therapy (21) or other tumoral lesions (22). Compared with FS examination as "gold method for diagnosis of BCC" in study of Baba et al (21) the sensitivity and specificity of TST for margin evaluation was 1.00 (95% CI = 1.00 -1.00) and 0.99 (95% CI = 0.98 -1.00), whereas positive and negative predictive values and diagnostic accuracy were 0.94 (95% CI = 0.84 -1.05), 1.00 (95% CI = 1.00 -1.00), and 1.00 (95% CI =0.99 -1.00), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Cytology is very important to distinguish between the two autoimmune blistering diseases (15). In pemphigus, cytology reveals numerous single or loosely adherent clumps of acantholytic cells (16). If the test is positive for acantholytic cells, direct immunofluorescence test on smear can be performed (17).…”
Section: Discussionmentioning
confidence: 99%